High-efficiency low-crosstalk dielectric metasurfaces of mid-wave infrared focal plane arrays - Akın, Onur (2017)
High-resolution compact-size focal plane arrays (FPAs) suffer the fundamental geometrical tradeoff between the optical resolution (pixel size miniaturization) and the optical crosstalk (spillover of neighboring pixel focusing). For FPAs, our previously reported metallic metasurfaces reached an unprecedented level of crosstalk suppression. However, practical utilization of these metallic microlens arrays has proved to be intrinsically limited due to the low device efficiency (of the order of 0.10) resulting from the fundamental absorption losses of metals and their cross-polarization scheme. Exceeding this limit, here we show highly efficient microlens designs enabled by dielectric metasurfaces for mid-wave infrared (MWIR) operation. These dielectric MWIR FPAs allow for a substantially high device efficiency over 0.80 without compromising the optical crosstalk performance. Systematically studying dielectric nanoantennas of silicon nanodisks that do not dictate the cross-polarization scheme using full-wave solutions, we found that the optical crosstalk is suppressed to low levels ≤≤ 3.0% while sustaining the high efficiency. A figure-of-merit (FoM) defined for the device performance as the focusing efficiency per optical crosstalk times the f-number achieves 84, which is superior to all other types of MWIR FPAs reported to date, all falling below a maximum FoM of 70. These findings indicate that the proposed approach can pave the way for the practical usage of metasurface microlens arrays in MWIR.